Out of China: distribution history of Ginkgo biloba L. - Zhao, Yunpeng; Paule, Juraj; Fu, Chengxin; Koch, Marcus (Taxon, 2010)
Abstract Gingko biloba L. is one of the most mysterious plant species, which continues to attract the interest of scientists and the public since many centuries. However, our knowledge of its evolutionary history and worldwide distribution is limited. Herein we are combining evidence from a previous phylogeographic analysis of Ginkgo biloba's range in China using cpDNA and AFLPs with new data from old, early introduced in Korea, Japan, Europe and Northern America with the aim to unravel the early human?mediated introduction history of this species. We provide evidence that Ginkgo biloba reached Japan via different routes from China during the last two millennia most likely by human?mediated dispersal. Based on AFLP data, all individuals originally introduced to Europe and North America (e.g., by Kaempfer in Europe in the 1720s) are genetically similar to one of the Korean accessions raising, the question of the validity of the origin of Kaempfer's original material, which was said to be brought from Japan to Europe in the early 18th century. Multiple introduction into Korea and Japan in concert with an out?crossing mating system has maintained high levels of gene diversity; this is also true for the European and North American trees. In addition, the trees outside the original Chinese Pleistocene refugia, due to their relatively small gene?pool, have a reduced number of AFLP fragments and no exclusive alleles.
First published: 01 April 2010
Gesehen am 12.03.2024